2014
DOI: 10.1158/0008-5472.can-14-1702
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Suppresses Leptin Stimulation of Cancer Growth through microRNA

Abstract: Obesity is a pandemic and major risk factor for cancers. The reduction of obesity would have been an effective strategy for cancer prevention, but the reality is that worldwide obesity has kept increasing for decades, remaining a major avoidable cancer risk secondary only to smoke. The present studies suggest that vitamin D may be an effective agent to reduce obesity-associated cancer risks in women. Molecular analyses showed that leptin increased human telomerase reverse transcriptase (hTERT) mRNA expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Our published studies have documented an important role for 1,25D 3 and EB1089 in suppressing EOC growth in multiple human EOC cell lines both in vitro [15,16,23] and in vivo in mouse tumor models [17,18,43]. This study is the first to reveal a role for 1,25D 3 in suppressing EOC invasion.…”
Section: Discussionsupporting
confidence: 51%
“…Our published studies have documented an important role for 1,25D 3 and EB1089 in suppressing EOC growth in multiple human EOC cell lines both in vitro [15,16,23] and in vivo in mouse tumor models [17,18,43]. This study is the first to reveal a role for 1,25D 3 in suppressing EOC invasion.…”
Section: Discussionsupporting
confidence: 51%
“…Another mechanism by which leptin is thought to promote cancer development is via human telomerase reverse transcriptase (hTERT) expression. This was suppressed by treatment with activated vitamin D 3 via induction of miR-498 in cell line models [102].…”
Section: The Role Of Leptin In the Tumour Microenvironmentmentioning
confidence: 99%
“…Reactions were run with the following parameters: 95°C for 3 minutes followed by 40 cycles of 95°C for 10 seconds, 55°C for 1 minute and GAPDH was run as a control for CYP24A1 expression. ΔCt values and fold of induction were calculated as described previously [12]. Each data point represents three independent analyses (n=3) presented as mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Our published studies in ovarian cancer have shown that 1,25D3 inhibits cancer growth by arresting cells at specific cell cycle checkpoints [79]. Further analyses have demonstrated that 1,25D3 induces microRNA target genes to decrease telomerase expression for cell death induction [10, 11] and to inhibit leptin and estrogen-induced tumor growth [12], suggesting that 1,25D3 has an important role in cutting down obesity-associated cancer risks in women [13]. More recent studies have shown that ovarian cancer invasion is suppressed by 1,25D3 through the cooperative actions of epithelial and stromal VDR [14].…”
Section: Introductionmentioning
confidence: 99%